2016
DOI: 10.18052/www.scipress.com/ilns.56.7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gas Flaring on the Physicochemical and Microbiological Quality of Water Sources in Egbema, Imo State, Nigeria

Abstract: Abstract. This study evaluated the effects of gas flaring on the physico-chemical and microbiological characteristics of water sources at Egbema, Imo State, Nigeria. Surface and ground water samples from the area were compared with samples from Ihiagwa Autonomous Community in Owerri West, a non-gas flared community. Both water sources were then compared with WHO standards for drinking water. The results revealed that water sources from the gas flared area have high levels of temperature, total chlorine, nitrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
2
3
0
Order By: Relevance
“…( Standards Organization of Nigeria, 2007 ) Temperature, turbidity, chlorine, dissolved oxygen, magnesium, total coliform, fecal coliform, oil/grease and TPH values were all found to be higher than the national drinking water standard. This finding is corroborated by the research findings of Braide et al . (2016) and Ugwoha et al .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…( Standards Organization of Nigeria, 2007 ) Temperature, turbidity, chlorine, dissolved oxygen, magnesium, total coliform, fecal coliform, oil/grease and TPH values were all found to be higher than the national drinking water standard. This finding is corroborated by the research findings of Braide et al . (2016) and Ugwoha et al .…”
Section: Discussionsupporting
confidence: 90%
“…(Standards Organization of Nigeria, 2007) Temperature, turbidity, chlorine, dissolved oxygen, magnesium, total coliform, fecal coliform, oil/grease and TPH values were all found to be higher than the national drinking water standard. This finding is corroborated by the research findings of Braide et al (2016) and Ugwoha et al (2017); who reported elevated temperatures in surface and groundwater water samples that were tested. Egwurugwu et al (2013) also reported elevated temperature, dissolved oxygen as well as magnesium levels in water samples obtained from gas flaring areas.…”
Section: Discussionsupporting
confidence: 81%
“…The values recorded in this study had some similarity with previous studies on water quality of some surface water in the Niger Delta. The value of total fungi ranged from 3.0 × 10 3 -3.7 × 10 4 CFU/ml in Otamiri river, Imo state [23], 2.1 × 10 3 -7.8 × 10 5 CFU/ml in Otamiri stream, Imo State [24], 2.12-2.22 × 10 2 CFU/ml in a Surface water in Krakrama community, Rivers state [25] and lower than values from Ogbekpan and Ikpoba Rivers, Edo state [26] which range from 3.10-3.20 × 10 5 CFU/ml in). The variations observed could be due to difference human activities in the water ways.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the fungi isolates identified in this study have been reported in some other studies on surface water in some part of the Niger Delta region of Nigeria. For instance, Braide et al [24] reported the occurrence Penicillium, Geotrichum, Aspergillus, Mucor, Rhizopus species, Candida albicans and Saccharomyces cerevisiae in Otamiri stream, Imo State. Idibie et al [26] reported Trichoderma, Mucor, Penicillium and Aspergillus species.…”
Section: Resultsmentioning
confidence: 99%
“…Gas flaring contributes to greenhouse gases through methane (CH4) and carbon dioxide (CO2). The flare pollutes methane and transforms it to 90-98% CO2 which is directly discharged into the climate (Braide, Nwachukwu, Adeleye, & Egbadon, 2016).…”
Section: Environmental and Health Effect Of Gas Flaring In Nigeriamentioning
confidence: 99%